Letter (copy) : Spanish Fund - Parkin, E. G.
041-0166-001 EP/EK/476. Finance. 4th September, 1936. Dr. C. Brook, Spanish Medical Unit, 24-28, New Oxford Street, London, W.C.1. Dear Dr. Brook, SPANISH FUND. We have received from Mrs. Palmer of 24, Onslow Avenue, Richmond the enclosed Spanish currency which she desires shall be credited to the funds of the Medical Unit. Will you kindly acknowledge receipt, direct to Mrs Palmer. Yours sincerely, Accountant. Currency. 292/946/41/166